The impact of the COVID-19 pandemic on the urology practice in a large tertiary hospital - Dündar, Gökçe; Erkan, Anıl (The European Research Journal, 2022)
Objectives: We aimed to reveal how four different areas that are important in the functioning of the urology clinic (outpatient clinic, inpatient clinic, operating room, and consultations) were affected during the COVID-19 pandemic. Methods: Patients admitted to the surgical branches between March 11, 2018 and March 10, 2021 were retrospectively evaluated in terms of their demographic data. The data between these dates were analyzed by dividing the patients into three groups as Groups A, B, and C for the pandemic period, the year before the pandemic, and two years before the pandemic, respectively. Results: A total of 1,222,967 patients were included in the study. During the pandemic period, the number of urology outpatient clinic admissions decreased by more than half compared to the previous years (37,471, 93,582, and 89,031 for Groups A, B, and C, respectively). Admissions to the urology inpatient clinic decreased both numerically and proportionally when compared to the other surgical branches (1,301 [5.1%] for Group A, 3,884 [7.7%] for Group B, and 3,761 [7.7%] for Group C]). While the mortality rate did not change proportionally in the urology clinic in all groups (0.3%), it increased both numerically and proportionally in all surgical branches (339 [1.3%], 304 [0.6%], and 256 [0.5%]). Conclusions: Admissions to the urology clinic were determined to have decreased during the pandemic compared to the pre-pandemic period, especially due to restriction measures taken by countries and concerns about the unknowns of the disease. As a result of this decrease, the number of operations and the number of hospitalized patients were also reduced. Although the mortality rate was not affected in the short-term follow-up of patients, long-term outcomes remain uncertain.